Analysis of Graduate Relevance to Program Learning Outcome Mechanical Engineering in State University of Surabaya - Heru Arizal; Tri Hartutuk Ningsih; Ali Hasbi Ramadani; Ika Nurjannah; Husni Mubarok (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
The college is one of the create of professional and qualified Human resource.. Universities must develop following the development needs of the business world and the industrial world. The purpose of this study was to analyze the relevance of Mechanical Engineering graduates to the Program Learning Outcome and as material for curriculum evaluation. The subjects of this research were 120 graduates in 2019 and 2020. The technique of collecting data was using a questionnaire through the State University of Surabaya Tracer Study web. The data is then analyzed using quantitative descriptive. As many as 55.83% of alumni are already working, 32.5% are not working, 10% are entrepreneurs, and the rest are continuing their education. The waiting time for graduates to get a first-time job takes an average of 4.49 months. The total relationship between the field of work and the field of education has a very tight, tight and pretty tight relationship of 77.5%. The profile of a mechanical engineering graduate is to become a mechanical engineer. The number of graduates who match the graduate profile is 61.2%. The competence of graduates is still below the competencies needed by the business and industrial. From the data above, we can conclude that graduates from the mechanical engineering study program are relevant to the established Program Learning Outcome.